Properties of Particleboard and Particle-Filled Thermoplastic Composite from Bamboo (Gigantochloa Scortechinii) - Kasim, Jamaludin (1999)
The mensurational attributes of culm basal diameter, weight and volume (except for culm wall thickness) were found to be significantly affected by age. Initial moisture content was observed to decrease while oven dry density increases significantly with age and culm portion. Cold water, hot water and alkali solubles were significantly influenced (p < 0.05) by the age and culm portion while the holocellulose content increased significantly (p < 0.05) with age but remained almost constant with culm height. In the manufacture of single-layer urea formaldehyde particleboard, all the board properties were observed to be significantly influenced at p < 0.05 by the main factors of age, particle size, resin and wax content. For the three-layer particleboard, the age of culm, core particle size and wax content had significant effects on all the board properties. Single-layer melamine urea-formaldehyde particleboards manufactured from vanous age culms varied significantly (p < 0.05) in all the mechanical and physical properties with age (except for internal bond), resin content, particle size and wax addition. For three-layer particleboards, age showed significant effects on all the board properties (except for modulus of rupture, modulus of elasticity and screw withdrawal surface), while core particle size significantly affected all the board properties. Wax addition improved the board dimensional stability but decreased the mechanical properties (except for modulus of elasticity). Bamboo-filled thermoplastic composite board properties varied significantly with age of culm, particle size, filler loading and maleated anhydride polypropylene addition. The bamboo density and its chemical properties affected some of the particleboard properties but their influence on the final bonding of the board were neglegible. However, bamboo-filled thermoplastic composite board properties were not affected by the variation in the chemical composition of the material. Regardless of age of bamboo, the bamboo particles were found to be suitable materials for the manufacture of particleboards and thermoplastic composites.